Improving Learners’ Speaking Skill through Video-Assisted Project Based Learning - Kasdianti, Evi; Tusino, Tusino; Setiyono, Junaedi (Department of English Language Education, Universitas Muhammadiyah Purworejo, Indonesia, 2024)
This study investigates the improvement of Video Assisted Project-Based Learning (VAPBL) in improving learners' speaking skills. While VAPBL, has been employed in many studies, the development of learners' speaking skills in terms of fluency, accuracy, and coherence has received less attention in the literature. Twenty-two learners from the language class of Secondary School, participated in the study. The investigation employed Classroom Action Research design to measure the outcome of VAPBL on learners' speaking proficiency. The two cycles involved selecting appropriate video materials and designing project-based learning activities aligned with curriculum objectives. There are two cycles in this research and each cycle consist of three meetings. During the application phase, learners engaged in VAPBL activities over a specified period, including watching videos, participating in discussions, and completing project-based tasks. The findings revealed a significant advancement in learners' speaking abilities following the application of VAPBL. Moreover, in the questionnaire the learners’ perception have positive outcome of VAPBL in language learning activities. This study underscores the importance of interactive and collaborative learning environments facilitated by VAPBL in enhancing learners' speaking skills.